2012
DOI: 10.1007/s11325-012-0761-8
|View full text |Cite
|
Sign up to set email alerts
|

Influence of CPAP treatment on airway and systemic inflammation in OSAS patients

Abstract: CPAP therapy has primarily a relevant impact on airways, and nitrotyrosine levels correlated well with severity of OSAS. This treatment decreases both inflammation and oxidative stress levels in airways in OSAS patients. Also, this treatment helps to decrease systemic oxidative stress levels in serum.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
51
1

Year Published

2013
2013
2022
2022

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 71 publications
(53 citation statements)
references
References 27 publications
1
51
1
Order By: Relevance
“…22 Additionally, CPAP relieves airway obstruction and hypoxia, as well as decrease airway and systemic inflammation and the levels of OSA induced inflammatory mediators. 23 CPAP treatment decreased platelet activation. Adenosine diphosphate-induced platelet aggregability increased significantly in patients with moderate-to-severe OSA compared to that in controls; CPAP treatment improves platelet aggregability in these patients.…”
Section: Discussionmentioning
confidence: 90%
“…22 Additionally, CPAP relieves airway obstruction and hypoxia, as well as decrease airway and systemic inflammation and the levels of OSA induced inflammatory mediators. 23 CPAP treatment decreased platelet activation. Adenosine diphosphate-induced platelet aggregability increased significantly in patients with moderate-to-severe OSA compared to that in controls; CPAP treatment improves platelet aggregability in these patients.…”
Section: Discussionmentioning
confidence: 90%
“…CPAP relieves airway obstruction and reduces hypoxia and inflammation [34]. CPAP treatment decreases platelet aggregability [35].…”
Section: Discussionmentioning
confidence: 99%
“…Much evidence demonstrates that treatment of OSA, including CPAP or surgery, can reduce inflammation and oxidative stress. 7,44,45 A recent meta-analysis of 35 studies involving 1,985 patients with OSA also confirmed that CPAP therapy could partially suppress systemic inflammation and there are differences among the various inflammatory markers such as CRP, IL-6, IL-8, and TNF-α. 7 However, CPAP is underused as a therapy for OSA even though investigators have demonstrated that CPAP may reduce the risk of atrial fibrillation or stroke.…”
Section: 9-11mentioning
confidence: 89%